2D Barcode Image Decoding. (11th December 2013) - Lin, Jeng-An; Fuh, Chiou-Shann
Abstract : Barcode technology is one of the most important parts of Automatic Identification and Data Capture (AIDC). Quick Response code (QR code) is one of the most popular types of two-dimensional barcodes. How to decode various QR code images efficiently and accurately is a challenge. In this paper, we revise the traditional decoding procedure by proposing a serial of carefully designed preprocessing methods. The decoding procedure consists of image binarization, QR code extraction, perspective transformation and resampling, and error correction. By these steps, we can recognize different types of QR code images. The experiment results show that our method has better accuracy than Google open-source 1D/2D barcode image processing library Zxing-2.1. Moreover, we evaluate the execution time for different-size images. Our method can decode these images in real time.